БАЗАР ЭКОНОМИКАСЫНА ДӘСЛЕПКИ ӨТИЎ ДӘЎИРИНДЕ ҚАРАҚАЛПАҚСТАНДА САНААТ ҚӘРҲАНАЛАРЫНЫҢ СЫРТҚЫ ЭКОНОМИКАЛЫҚ БАЙЛАНЫСЛАРЫ ТАРИЙХЫНАН - Сарыбаев, А.К.; Ктайбеков, А.А. (SCIENCE and SOCIETY, 2025)
This article discusses the development of foreign economic activity of the Republic of Karakalpakstan. The processes of using investments from foreign countries in industrial enterprises of the region during the initial period of transition to a market economy are shown.
Keywords: market economy; economic situation; onesided economic development; development of industrial potential; foreign investments; joint factories